How Informal Institutions Matter Evidence from Turkish Social and Political Spheres - Sarigil, Zeki (University of Michigan Press, 2023)
In How Informal Institutions Matter, Zeki Sarigil examines the role of informal institutions in sociopolitical life and addresses the following questions: Why and how do informal institutions emerge? To ask this differently, why do agents still create or resort to informal institutions despite the presence of formal institutional rules and regulations? How do informal institutions matter? What roles do they play in sociopolitical life? How can we classify informal institutions? What novel types of informal institutions can we identify and explain? How do informal institutions interact with formal institutions? How do they shape formal institutional rules, mechanisms, and outcomes? Finally, how do existing informal institutions change? What factors might trigger informal institutional change? In order to answer these questions, Sarigil examines several empirical cases of informal institution as derived from various issue areas in the Turkish sociopolitical context (i.e., civil law, conflict resolution, minority rights, and local governance) and from multiple levels (i.e., national and local).